2012
DOI: 10.1007/s00330-012-2591-2
|View full text |Cite
|
Sign up to set email alerts
|

T1rho and T2 relaxation times for lumbar disc degeneration: an in vivo comparative study at 3.0-Tesla MRI

Abstract: T1rho is better suited for evaluating AF in degenerated disc than T2. In NP, T1rho and T2 decrease in a similar pattern following disc degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
3
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 29 publications
6
68
3
1
Order By: Relevance
“…For future studies if Dslow and PF of liver fall out of reasonable range, causes should be investigated. Imperfection in data acquisition or processing method may lead to reduced sensitivity in detecting tissue changes (65,66). Systematic bias may also be introduced during imaging due to difference of hardware being used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For future studies if Dslow and PF of liver fall out of reasonable range, causes should be investigated. Imperfection in data acquisition or processing method may lead to reduced sensitivity in detecting tissue changes (65,66). Systematic bias may also be introduced during imaging due to difference of hardware being used.…”
Section: Discussionmentioning
confidence: 99%
“…The longer the echo time, the greater the signal decays at low b values, which indicates the increase of estimated PF. This phenomenon is due to the faster transverse relaxation of the tissue compartment signal (i.e., the liver), which increases the signal fraction of Quant Imaging Med Surg 2017;7(1): [59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78] qims.amegroups.com Table S1. the vascular component.…”
Section: Ivim Parameters Of Healthy Liver In Published Literaturesmentioning
confidence: 99%
“…Elevated T1rho was correlated with the amount of collagen deposition in biliary duct ligation induced liver fibrosis (1). However, fiber tissue is not necessarily associated with higher T1rho inherently (16), as shown in intervertebral disc degeneration studies (17,18). Liver fibrosis, depending on its causes, is associated with a number of complicated pathological processes, including steatosis, hepatocellular ballooning, and inflammation (19,20).…”
mentioning
confidence: 99%
“…In addition, T1ρ relaxation times correlated significantly with the water content in the intervertebral lumbar disc [7]. In comparison with T2 mapping, earlier studies suggest that T1ρ might be more sensitive to early degenerative changes, especially in the annulus fibrosus [11,12]. T1ρ therefore appears to be a promising noninvasive tool for detecting early disc degeneration in vivo.…”
Section: Introductionmentioning
confidence: 90%
“…The main reason for this decision was to keep the total examination time for the volunteers (who underwent a standardized physical examination, structured interview and a standardized questionnaire in addition to MRI) as short as possible to ensure their willingness to take part in the study. The lack of a morphologic parameter such as the Pfirrmann Grade is justified as studies in the past have shown high correlations between T1ρ and degeneration status in symptomatic patients [6,11,12]. Finally, the ability of T1ρ to quantify disc degeneration was assumed [11 -13].…”
Section: Limitationsmentioning
confidence: 99%